Book review: Ian Klinke: Life, Earth, Colony: Friedrich Ratzel’s Necropolitical Geography - Korf, Benedikt (ERDKUNDE, 2024)
Klinke, Ian (2023): Life, Earth, Colony: Friedrich Ratzel’s Necropolitical Geography. University of Michigan Press. Ann Arbor. 329 pp, 16 illus. ISBN: 978-0-472-05617-0 (paperback, 39.95), 978-0-472-90351-1 (open access), 978-0-472-07617-8 (hardcover, 85.00).